Guru PAI Dalam Implementasi Pendidikan Inklusi Pada SMPN Di Kabupaten Tabalong - Mof, Yahya; Mizani, Hilmi; Ramli, M.; Fauzinor, Akhmad (el Buhuth: Borneo Journal of Islamic Studies, 2021)
Inclusion education has been implemented in Tabalong Regency since 2011. PAI teachers as the spearhead of the implementation of education in schools, are very decisive in implementing an inclusive education system in schools. This study aims to reveal the role of Islamic Religious Education teachers in the implementation of inclusive education in junior high schools in Tabalong Regency. For this type of research using qualitative descriptive research, the subjects in this study are PAI teachers and students. Data collection techniques use observation, interview and documentation instruments. The results of the data collection are then analyzed in a qualitative descriptive manner. The research found that the role of PAI teachers in the implementation of inclusive education in junior high schools in Tabalong Regency is still minimal. PAI teachers still use the regular curriculum, namely the 2013 curriculum and do not make special RPP in the form of PPI. Adjustment to ABK by modifying learning methods and evaluating learning. Because since the implementation of the inclusion education system in SMPN in Tabalong Regency has not been equipped with guidance teachers Special (GBK) and teachers at SMPN have not received special training on mentoring for children with special needs. therefore, the implementation of inclusion education in Tabalong Regency is still not optimal